Impact of Working Capital on Financial Performance of Gulf Cooperation Council Firms - Kumaraswamy, Sumathi (International Journal of Economics and Financial Issues, 2016)
As an extension of prior literatures that proved the relationship between working capital and firm performance, the present study aims to explore the impact of working capital on the firm performance of Cement Manufacturing GCC firms for a period of 2008-2014. Four hypotheses pertaining to working capital components were investigated using linear regression models. The study identified positive relationship between inventory conversion period, average payment period with profitability and a negative relationship amid average collection period and firm profitability. The result of regression model indicates average collection period and inventory conversion period to be the most significant factors followed by average payment period. It shows that the profitability of the GCC cement manufacturing firms are greatly influenced by the average collection period and high inventory levels. Keywords: Working capital, Profitability, GCC, Average Collection Period, Inventory Conversion Period, Average Payment Period JEL Classifications: M1, M4